2019
DOI: 10.18805/ijar.b-1063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age at first calving and other non-genetic factors on longevity and production traits in Holstein cattle under Vojvodina Province condition, Serbia

Abstract: The effect of age at first calving (AFC) and various non-genetic factors i.e. season of calving, farm and system of housing on longevity and production traits were investigated. Longevity traits were studied using total lifetime (TL), length of productive life (LPL) and number of lactations (NL) while production was researched using lifetime milk yield (LMY). Data of 2037 Holstein dairy cows were provided by the main breeding organizations at the Faculty of Agriculture, University of Novi Sad. The average valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In addition, cows first calving at <21 month of age have a high risk of culling due to dystocia and the high elimination is related to the quota system that exists in Canada (Nilforooshan and Edriss, 2004). Anim et al (2020) analyzed different lactations recordings and found that productive life of dairy cows gradually decrease with the increasing of the age of the first calving, especially for cows calving at an age over 29 months. Mossa and Ireland (2019) found that cows had low fertility, low milk yield, and a high elimination risk with low and high follicle numbers.…”
Section: Longevity and Reproductive Performancementioning
confidence: 99%
“…In addition, cows first calving at <21 month of age have a high risk of culling due to dystocia and the high elimination is related to the quota system that exists in Canada (Nilforooshan and Edriss, 2004). Anim et al (2020) analyzed different lactations recordings and found that productive life of dairy cows gradually decrease with the increasing of the age of the first calving, especially for cows calving at an age over 29 months. Mossa and Ireland (2019) found that cows had low fertility, low milk yield, and a high elimination risk with low and high follicle numbers.…”
Section: Longevity and Reproductive Performancementioning
confidence: 99%
“…The findings contradict findings ofKrogmeier et al (2015) andFuerst-Waltl et al (2019) for Fleckvieh breed. These authors revealed better traits in cows seasonally grazed Kučević et al (2020). reported similar lifetime milk yield for Holstein cows in Serbia (2% difference in favour of Holstein cows not grazed in Slovakia).…”
mentioning
confidence: 72%
“…Hence, factors of farm and local conditions were found to influence age at first calving (Castillo Badilla et al, 2011;Valchev et al, 2020). Breed, housing system, herd size, herd production level and management criteria were reported to influence longevity and lifetime performance traits (Jankowska et al, 2014;Kučević et al, 2020). Moreover, grazing has been reported to have a significant effect on these traits as mentioned by Krogmeier et al (2015).…”
Section: Introductionmentioning
confidence: 94%